Načelo trajnosti v gozdarskem načrtovanju - Bončina, Andrej (Zbornik gozdarstva in lesarstva, 2000)
Sustainable forest management (SFM) can be described by criteria and indicators. Biodiversity conservation is one of the main SFM criteria. The main task of forest planning is to organise multiple forest use according to natural conditions. The concept of sustainability should be respected throughout the whole process of forest planning. Assessment of SFM is a constituent part of the planning phase - assessment of conditions, enabling clear problem definition, which represents a starting point for a new plan. Assessment of SFM is based on indicators, which have a large indicative value for SFM criteria; therefore their values have to be verifiable and available in the forestry information system. In addition, indicators have to reflect current changes in forest management praxis. Actual indicator values can be either compared to norm values (verifiers) or one can merely monitor their changes over time. For affirmation of the sustainability principle in forestryplanning it is important that (1) public and forest owners are involved into goal setting, (2) goals are in accordance to natural conditions,(3) forestry planning includes different forestry branches (silviculture, skidding, etc) and (4) planning is organised on different spacelevels. Some problems regarding SFM in Slovenia are defined.
Keywords: biodiverziteta; biološka raznolikost; forest; gospodarjenje z gozdovi; gozd; kriteriji; načrtovanje